(untitled) (Research, Society and Development, 2020)
Dragon’s blood, native species from South America, has therapeutic properties scientifically proved. This study had the objective of developing a protocol for in vitro establishment and plantlets acclimatization from zygotic embryos, since researches with species are incipient. Culture media (MS, WPM, QL and N6) were assessed, without and with activated charcoal (2 g L-1). It was observed the percentage of developed embryos from 83% to 100% and the effect of medium composition for plant height and leaf number in vitro. The plantlets were acclimatized with 100% of survival rate, and for treatments from in vitro culture only the culture medium influenced diameter and plant height. The WPM and QL formulations without activated charcoal are indicated for in vitro culture of embryos and acclimatization of Dragon blood. The suggested methodology represents an important strategy for reproduction, physiological study and preservation of species.